Injury and illness prevention practices in Qatar`s professional football clubs—implementation of the IP2 NetWork - Hassanmirzaei, B.; Schumacher, Y. O.; Tabben, M.; Chaabane, M.; Chebbi, S.; Daoud, R.; Heitor, M.; Miladi, R.; Rekik, R. N.; Skhiri, O.; Bahr, R. (BMJ Open Sport & Exercise Medicine, 2025)
Background The Aspetar Sports Injury and Illness Prevention Programme introduced the Aspetar IP2 NetWork, a customizable injury prevention programme for professional football clubs in Qatar during the 2020/2021 season. It includes 23 focus areas selected by stakeholders to prevent sports-related health issues.